Desenvolvimento de fases estacionárias baseadas na imobilização térmica do dodecanoato de celulose sobre sílica para CLAE-FR e suas aplicações em análises de compostos polares e enantioméricos - Vieira, Andressa Tironi (2018)
The separation of some mixtures of compounds, such as highly polar compounds, are still a challenge for liquid chromatography. The need for selective separation materials for these compounds has been the search for extension of technique application field. The goal of this work was to develop a HPLC stationary phase based on a cellulose derivative, cellulose dodecanoate (DoDC), immobilized onto silica particles to act in the fast and efficient separation of substances that are difficult to analyze in commercial phases. The polymer was synthesized and used as a polymer coating stationary phases, Si(DoDC). The phases were characterized physicochemical and chromatographically. The physicochemical characterization results indicated that the DoDC was synthesized with a cellulose substitution degree of 1.7 and efficiently immobilized onto silica surface. Through a factorial design it was possible to find the best preparation condition of Si(DoDC) phases in terms of polymer load, temperature and immobilization time. Infrared spectra confirmed the presence of the cellulose derivative in Si(DoDC) phase, through C=O and C-H stretches, characteristics of polymer. Scanning Electron Microscopy images indicated that, even after DoDC immobilization on silica, the particles maintained morphological characteristics suitable for particle packaging in stainless steel columns. From the chromatographic analyzes, it was verified that the Si(DoDC) phase acts in reverse phase mode by separation of substances by mechanisms of hydrophobic interactions due to the 12-carbon dodecanoate group. The Si(DoDC) phase presented intrinsic steric selectivity, which can be attributed to cellulose chirality. Si(DoDC) phase was successfully applied in the separation of highly polar drugs, enantiomers of a pharmaceutical compound and positional isomers of the linear alkylbenzene sulfonic anionic surfactant (LAS). In conclusion, the use of cellulose dodecanoate as a stationary phase for high-performance liquid chromatography in reverse phase mode was successful and presents a wide range of possibilities of application in the separation of several classes of compounds